SEJARAH PERKEMBANGAN TAFSIR AL-QUR’AN PADA ABAD KE VII H - Miswar, Andi (Rihlah: Jurnal Sejarah dan Kebudayaan, 2017)
The VIIth century is known as the mutaakhhirin period in the development of Qur’anic interpretation. In this era of interpretation activities experienced a very significant development, for example from the form of bi al-ma’tsur (riwayah) exagesis to the form of dirayah (al-ra’yu) exagesis that is interpretation based on ijtihadiy as contained in Mafatih al-ghaib / Al-kabir exagesis by al-Razi in the style of philosophy in which there are philosophical views of the Qur’anic statements. On the other hand the exagesis book was published in that century is the interpretation of Anwār al-tanzil wa Asrār al ta’wil by Al-Baidhawi who uses the source of interpretation bi al-Ra’yi exagesis with the style of ilmiy exagesis who tends to use logical argument and explore various problems of science, and the exagesis that has the form of al-isyariy (intuition) with shufiy interpretative style is Ibn ’Arabi’s exagesis . The tendency of exagesis mostly impluenced by their personal understanding, school of thought, and qualifications of their knowledge.